The problem-centred interview principles and practice - Witzel, Andreas (SAGE, 2012)
The problem-centered interview is an approach to designing and conducting a research interview and remains relatively unknown to the Anglo-Saxon market. This book is an attempt to bring the work of the Bremen School to a wider international audience. It offers an introduction to qualitative interviewing.